A multi-component assessment model for monitoring training distress among athletes - Main, L.; Grove, J. R. (European Journal of Sport Science, 2009)
We report the initial validation of a multi-component assessment model for monitoring training distress among athletes. The model combines measures of mood disturbance with measures of perceived stress and symptom intensity. Altogether, 492 athletes completed the 10-item Perceived Stress Scale (PSS-10; Cohen et al., 1983), the 24-item Brunel Mood Scale (BRUMS; Terry et al., 2003), and a checklist of 19 symptoms associated with acute overtraining (Fry et al., 1994). Six training distress factors were identified by an exploratory factor analysis: "depressed mood", "perceived vigour", "physical symptoms", "sleep disturbance", "perceived stress", and "general fatigue". Comparisons of group means of these factors with a previously validated inventory were consistent with theoretical predictions and provided evidence of construct validity. Internal consistency of the subscales was also confirmed, with Cronbach alphas ranging from 0.72 to 0.86. Together, these findings suggest that this multi-component model provides a sound conceptual basis for the assessment of training distress among athletes